Bridging MoCs in SystemC Specifications of Heterogeneous Systems. (4th June 2008) - Damm, Markus; Haase, Jan; Grimm, Christoph; Herrera, Fernando; Villar, Eugenio
Abstract : In order to get an efficient specification and simulation of a heterogeneous system, the choice of an appropriate model of computation (MoC) for each system part is essential. The choice depends on the design domain (e.g., analogue or digital), and the suitable abstraction level used to specify and analyse the aspects considered to be important in each system part. In practice, MoC choice is implicitly made by selecting a suitable language and a simulation tool for each system part. This approach requires the connection of different languages and simulation tools when the specification and simulation of the system are considered as a whole. SystemC is able to support a more unified specification methodology and simulation environment for heterogeneous system, since it is extensible by libraries that support additional MoCs. A major requisite of these libraries is to provide means to connect system parts which are specified using different MoCs. However, these connection means usually do not provide enough flexibility to select and tune the right conversion semantic in a mixed-level specification, simulation, and refinement process. In this article, converter channels, a flexible approach for MoC connection within a SystemC environment consisting of three extensions, namely, SystemC-AMS, HetSC, and OSSS+R, are presented.